2022
DOI: 10.3390/foods11020238
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Superheated Steam Treatment on the Allergenicity and Structure of Chicken Egg Ovomucoid

Abstract: The aim of this study was to explore the effects of an emerging and efficient heating technology, superheated steam (SS), on the allergenicity and molecular structure of ovomucoid (OVM). OVM was treated with 120–200 °C of SS for 2 to 10 min. The allergenicity (IgG/IgE binding abilities and cell degranulation assay) and molecular structure (main functional groups and amino acids modification) changes were investigated. The IgG-binding ability of OVM decreased and the releases of β-hex and TNF-γ were inhibited a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Surface hydrophobicity is closely related to the conformation of protein, 33 which is an essential indicator of the binding ability between antibodies and antigens and plays an important role in assisting in epitope recognition. 34 It has been shown that roasting could induce the unfolding of the protein structure, and the internal hydrophobic amino acids were exposed to a non-polar microenvironment, which enhanced surface hydrophobicity and exposed more epitopes to increase IgG/IgE binding ability. The surface hydrophobicity decreased obviously after roasted + reverse-pressure sterilization (Figure 5D), which is a sign of protein aggregation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Surface hydrophobicity is closely related to the conformation of protein, 33 which is an essential indicator of the binding ability between antibodies and antigens and plays an important role in assisting in epitope recognition. 34 It has been shown that roasting could induce the unfolding of the protein structure, and the internal hydrophobic amino acids were exposed to a non-polar microenvironment, which enhanced surface hydrophobicity and exposed more epitopes to increase IgG/IgE binding ability. The surface hydrophobicity decreased obviously after roasted + reverse-pressure sterilization (Figure 5D), which is a sign of protein aggregation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, other allergens (e.g., ovomucoid) may be resistant to high temperatures. This fact explains why some individuals only present allergic symptoms/reactions to raw egg and/or foods containing raw egg, while others do to both raw and cooked eggs (even if subjected to a high-temperature cooking process) [ 29 ]. Thus, the results in Figure 5 elucidate that individuals hypersensitive to ovotransferrin should pay attention to the cooking process, which must be carried out at high temperatures or in an acidic medium.…”
Section: Resultsmentioning
confidence: 99%
“…Paper lower than that using other processing methods reported, which reduced it to about 60% and 70% of the original value, respectively. 18,33 Considering the fact that L-cysteine unfolded the ovomucoid molecule but the induced structural change did not reduce its IgE binding capacity, we speculated that its IgE reactivity reduction after glycation under the optimized conditions was due to sugar conjugation on its linear epitopes. The specific glycation sites of the ovomucoid after the optimized treatment were determined by HPLC-MS/MS.…”
Section: Food and Functionmentioning
confidence: 99%
“…17 This evidence suggests that the efficacy of glycation could be limited by the physicochemical properties of this allergen including heat stability, a high ratio of glycosylation (20-25%), and its singular conformation stabilized by nine pairs of disulfide bonds that are involved in the preservation of the IgE-binding capacity of this allergen. 18,19 In this work, we sought to determine whether a prior disruption of the ovomucoid disulfide bonds using L-cysteine may enhance the glycation of this allergen and modify its allergenicity. Moreover, the antioxidant properties of the ovomucoid samples before and after simulated infant and adult gastrointestinal digestion were also evaluated.…”
Section: Introductionmentioning
confidence: 99%